Electrical and Magnetic Properties of Strontium Ferrite and Barium M-Hexaferrite Based on Natural Iron Sand as Power Plant Generator Materials: A Systematic Review - Susilawati; Aris Doyan; Muhammad Taufik; Syarful Annam; Muhammad Ikhsan; Nuraini Rachma Ardianti (Jurnal Penelitian Pendidikan IPA, 2024)
Research in the field of materials, especially the magnetic properties of materials, continues to increase. This research aims to identify and analyze research trends of electrical and magnetic properties of strontium ferrite and barium m-hexaferrite based on natural iron sand as power plant generator materials. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research electrical and magnetic properties of strontium ferrite and barium m-hexaferrite based on natural iron sand as power plant generator materials that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2015 to 2024 has experienced ups and down. There are many documents in the form of articles, chapters, preprints, monograph and edited books that discuss research about electrical and magnetic properties of strontium ferrite and barium m-hexaferrite based on natural iron sand. Key words that are often used in research about it are synthesis, characterization, permanent magnet, etc.